Migrant shorebirds at Península Valdés, Argentina: Report for the year 2000 - Bala, Luis Oscar (2002)
We report observations of migrant shorebirds on the beaches of Península Valdés, Chubut, Argentina (42°30'S, 64°00'W), during their northward stopover in the year 2000. This follows a report for the 1999 season, which covered just one site, Fracasso beach, published in Bala et al. (2001).